Choral masterworks : a listener's guide - Steinberg, Michael, 1928-2009 (OUP E-Books., 2005)
Michael Steinberg's highly successful listener's guides - "The Symphony" and "The Concerto"--Have been universally praised for their blend of captivating biography, crystal clear musical analysis, and delightful humor. Now Steinberg follows these two greatly admired volumes with "Choral Masterworks: A Listener's Guide", the only such guide available to this most popular of musical forms. Here are more than fifty illuminating essays on the classic choral masterworks, ranging from Handel's "Messiah", Bach's "Mass in B Minor", and Beethoven's "Missa Solemnis", to works by Haydn, Brahms, Mendelssohn, and many others. Steinberg spans the entire history of classical music, from such giants of the Romantic era as Verdi and Berlioz, to leading modern composers such as Elgar, Rachmaninoff, Vaughan Williams, and Stravinsky, to contemporary masters such as John Adams and Charles Wuorinen. For each piece, Steinberg includes a fascinating biographical account of the work's genesis, often spiced with wonderful asides, such as the true story of Mozart's "Requiem"--Salieri had nothing to do with the composition of it, nor did he poison Mozart, who most likely died of rheumatic fever.; The author also includes an astute musical analysis of each piece, one that casual music lovers can easily appreciate and that musicians and more serious fans will find invaluable. The book also includes basic information such as the various movements of the work, the organization of the chorus and orchestra, and brief historical notes on early performances. More than twenty million Americans perform regularly in choirs or choruses. "Choral Masterworks" will appeal not only to concert goers and CD collectors, but also to this vast multitude of choral performers, an especially engaged and active community